PENGARUH PEMBERDAYAAN KARYAWAN DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL SEKRETARIAT PERUSAHAAN DAERAH PASAR KOTA DENPASAR - Fitriah, Fitriah; Sudibya, I Gede Adnyana (E-Jurnal Manajemen, 2015)
This research is influence of employe empowerment and job satisfacation to organizational commitm.. This research was conducted at Sekretariat Perusahaan Daerah Pasar Kota Denpasar di Jalan Sulawesi No 1 Lantai IV Pasar Badung. The respondents were 55 employees who have been propotiance random sampling . Path Analysis is used to test the amount of the contribution that is created from the free variable on the dependent variable . Statistical test tools got the result that the impact of employee empowerment on organizational commitment melaliu employee satisfaction and job satisfaction effect on commitment . ob satisfaction will increase the willingness of an employee to get a better chance to develop creativity , flexibility and autonomy over their own work .
Keywords: Employee empowerment, job satisfaction, organizational commitment